2008
DOI: 10.1007/s00701-008-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of embolization in radical surgery of renal cell carcinoma spinal metastases

Abstract: Metastasis size, extent of tumour, technical complexity of surgery and the completeness of preoperative embolization had an important effect on the amount of peroperative blood loss. The evaluation of the benefits of preoperative embolization only on the basis of blood loss is not an adequate method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Due to these inconclusive results, the present study systemically reviewed the effectiveness of PE in spinal metastases from a RCT and cohort studies and included six studies for meta-analysis. The pooled SMD of all studies showed no statistically significant difference between the PE and non-PE groups (p=0.09), but sensitivity analysis showed that the pooled results changed to a statistically significant difference when the study by Rehak et al 10 was omitted. Subgroup analysis showed that PE could significantly reduce IBL in patients with mixed primary tumor metastases (p=0.01) but did not significantly reduce IBL in patients with RCC metastases (p=0.90).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Due to these inconclusive results, the present study systemically reviewed the effectiveness of PE in spinal metastases from a RCT and cohort studies and included six studies for meta-analysis. The pooled SMD of all studies showed no statistically significant difference between the PE and non-PE groups (p=0.09), but sensitivity analysis showed that the pooled results changed to a statistically significant difference when the study by Rehak et al 10 was omitted. Subgroup analysis showed that PE could significantly reduce IBL in patients with mixed primary tumor metastases (p=0.01) but did not significantly reduce IBL in patients with RCC metastases (p=0.90).…”
Section: Discussionmentioning
confidence: 88%
“…Average IBL in the PE group ranged from 618 mL to 4827 mL (2894.7–4827.27 mL in RCC and 520.4–1650 mL in mixed primary tumors). The majority of studies reported that IBL in the control group was more than in the PE group; only the study by Rehak et al reported that IBL in the control group (1785±756 mL) was less than in the PE group (4750±2268 mL) 10. In the study by Rehak et al the average size of the metastases in the PE and non-PE groups was 92±70 cm 3 and 50±28 cm 3 , respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Für den Operateur ist dies besonders wichtig, da der intraoperative Blutverlust je nach Literaturangabe um ca. 1 bis 2 Drittel reduziert werden kann [23,24], weshalb diese Strategie zu empfehlen ist [24,25,26].…”
Section: Präoperative Embolisierungunclassified
“…However, embolization series of spinal tumors mainly discussed the intraoperative blood loss to evaluate the usefulness of interventional procedure rather than the perioperative complications [11][12][13]. In addition, some surgical series [14][15][16], in which embolization was used, reported on less than 30 cases and there were no large studies evaluating the rate of major complications for B. Tang and T. Ji contributed equally.…”
Section: Introductionmentioning
confidence: 97%